2011
DOI: 10.1111/j.1365-2850.2011.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigma experiences in bipolar patients: the impact upon functioning

Abstract: The aim of this study was to investigate the impact of self-rated stigma and functioning in patients with bipolar disorder in South Brazil. This is a cross-sectional study. Sixty participants with bipolar disorder were recruited from an outpatient Bipolar Disorder Program. Experiences with and impact of perceived stigma were evaluated using the Inventory of Stigmatizing Experiences. Functional impairment was assessed with the Functioning Assessment Short Test (FAST). Higher scores of self-perceived stigma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 67 publications
3
9
0
1
Order By: Relevance
“…One of our most important findings is that some residual symptoms have an impact on specific functional domains, a finding only outlined for residual depressive symptoms, cognitive impairment, and stigma in previous studies. In particular, residual depressive symptoms were found to be strongly associated with impairments in interpersonal and occupational functioning (45,46), cognitive dysfunction with impairments in cognitive and professional functioning (47), and stigma with impairments in interpersonal, cognitive, and leisure functioning (26,48,49). More generally, we found that some residual symptoms were associated with a characteristic pattern of functional impairment.…”
Section: Discussionsupporting
confidence: 48%
“…One of our most important findings is that some residual symptoms have an impact on specific functional domains, a finding only outlined for residual depressive symptoms, cognitive impairment, and stigma in previous studies. In particular, residual depressive symptoms were found to be strongly associated with impairments in interpersonal and occupational functioning (45,46), cognitive dysfunction with impairments in cognitive and professional functioning (47), and stigma with impairments in interpersonal, cognitive, and leisure functioning (26,48,49). More generally, we found that some residual symptoms were associated with a characteristic pattern of functional impairment.…”
Section: Discussionsupporting
confidence: 48%
“…Stigma is an expression of people's responses to individuals who possess some undesirable characteristics. It can be discrediting and involve prejudicial and discriminatory practices [32, 33]. In several studies stigma has been found to reduce social functioning [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Being treated as a person who cannot be trusted can increase the feeling of inferiority and shame. Thomé et al [33] demonstrated a correlation between stigma and poor functioning in bipolar disorder. Perceived stigma played a significant role in how the participants experienced their illness.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the general public endorse stigmatising attitudes towards people with BD (Wolkenstein and Meyer, 2008), few studies have focused exclusively on this diagnosis and stigma, or examined stigma experiences of people diagnosed with it (Brohan et al, 2010a;Hayward et al, 2002;Kelly and Jorm, 2007). However, perceived stigma is high amongst people with the diagnosis (Brohan et al, 2010b) and is associated with lower self-esteem in depressive episodes (Hayward et al, 2002), low autonomy, workplace difficulties, poor cognitive functioning, adverse financial issues, fewer interpersonal relationships (Thome et al, 2012;V azquez et al, 2011) and increased avoidance of social interactions . Having a mood disorder is also associated with an increased likelihood of endorsing stigma as a barrier to help-seeking (Alvidrez and Azocar, 1999).…”
Section: Stigma and Bdmentioning
confidence: 93%